Gal epitope expression and immunological properties in iGb3S deficient mice. Issue 1 (December 2018) - Shao, Anliang; Xu, Liming; Wu, Xi; Liu, Susu; Lu, Yan; Fan, Changfa
Abstract The Gal antigen is synthesized by glycoprotein galactosyltransferase alpha 1, 3 (GGTA1 ) or (and) isoglobotrihexosylceramide 3 synthase (iGb3S ). However, whetheriGb3S deletion changes Gal epitope expression and immunological properties in animals is still not clear. The objective of this study was to developiGb3S deficient mice, and characterize their Gal epitope expression and Gal epitope-related immunological properties.iGb3S gene knockout mice were generated on the C57BL/6 background using the bacterial artificial chromosome homology region recombination technique. Gal epitope expression in theiGb3S deficient mice was determined by using a monoclonal anti-Gal antibody. Immunological properties were analyzed by enzyme linked immune sorbent assay. It was found that Gal epitope expression was decreased from 5.19% to 21.74% in the main organs ofiGb3S deficient mice, compared with that of C57BL/6 wild type mice, suggesting that theiGb3S gene participated to Gal epitope expression. However, iGb3S deletion alone did not cause significant changes in the immunological properties ofiGb3S deficient mice with or without exogenous Gal antigen (Rabbit Red Blood Cell) stimulation. The data from this study suggest that theiGb3S gene likely contributes to Gal epitope expression, but may have a very weak effect on immunological properties of theiGb3S deficient mice.